The Architecture of an ‘Ultimate’e-Assessment System - Armenski, Goce; Gushev, Marjan (My University, 2009)
In the past two decades the area of e-learning was dominated by monolithic application silos. Modern Learning Management Systems (LMS) are facing the challenges for greater interoperability, flexibility, reusability, accessibility and manageability, as well as for sharing learning resources and components. Extensive research has been done in the field of sharing learning content and resources, but there is lack of theoretical and practical examples of systems sharing components and their functionality. Assessment is an important integral part of every learning process. A lot of software packages exist in the market to realize automated assessment, but most of them are stand alone applications without possibilities for interoperability, adaptability according to learner characteristics and possibilities for content and functionalities reuse. In this paper we present the architecture of an “ultimate” e-Assessment System. This System should be able to work as a standalone e-assessment application, be able to use and exchange content and components with other e-assessment systems, and at the same time it should be easily attachable to any existing applications in educational and business environments.
Keywords: e-Assessment, Service Oriented Architecture, e-Learning